Visual and non-visual effects of integrated lighting based on spectral information - Jin, Ling; Xue, Peng; Zhang, Lei; Wang, Jun; Shi, Jiaxin; Liang, Qingxuan; Cao, Xiaodong; Xu, Nan; Liao, Junhua (Building and environment, 2023)
Light meets the visual needs of the human body through the visual channel, and guides the physiological system of the human body to synchronize with the cycle of luminous environment through the non-visual channel, affecting emotions, sleep quality, alertness and even health. The indoor luminous environment of buildings where people spend more and more time is divided into two parts: artificial lighting and daylighting, both of which are separated from each other in terms of standards and research. However, integrated lighting scenes where daylight and artificial light exist at the same time are very common in real-life indoor environments, and the relationship between the two in integrated lighting and the impact of integrated lighting on non-visual effects remain unclear. In this study, the amount of daylight was manipulated by controlling sunshades in different artificial lighting environments, and the relationship between daylight and artificial light in integrated lighting was explored based on the subject evaluations. The results show that the direction and shading form have a significant impact on the perception of daylight, and the front facing direction has its particularity because it directly receives daylight. Additionally, artificial lighting settings with varying illuminance and correlated color temperature can also affect the perception of daylight. Furthermore, compared to artificial lighting alone, integrated lighting in sunny conditions can significantly increase circadian stimulus, which could improve daytime work efficiency. •37 subjects were recruited to judge when daylight dominates in integrated lighting.•Two forms of sunshade, upper sunshade and lower sunshade, are set.•Three levels of illuminance and four levels of CCT for artificial lighting are set.•Collect the perceptions of the subjects in integrated lighting using questionnaires.•Subjects' eye-level spectra were recorded and CS values were calculated.